FUZZY NEUTROSOPHIC RELATIONS - Arockiarani; Jency, Martina (International Journal of Research -GRANTHAALAYAH, 2016)
The focus of this paper is to present the concept of fuzzy neutrosophic relations. Further we study the composition of fuzzy neutrosophic relations with the choice of t-norms and t-conorms and characterize their properties.